Too much freedom and autonomy in the enactment of assessment? Assessment in physical education in Ireland. Issue 2 (3rd April 2017) - MacPhail, Ann; Murphy, Frances
Abstract : This paper sets out to outline current discussions in Ireland around teachers being responsible for assessing their own students' work, and the subsequent impact such a perspective is having (or not) on the delivery and assessment of physical education in Ireland. Our intention is to contribute to assessment considerations, while acknowledging the nuances of the Irish education context, and the positioning of physical education within such nuances. This discussion is particularly timely given the very recent endorsement for the introduction of the new Leaving Certificate Physical Education as a full optional subject. We begin by discussing more specifically assessment in Irish primary and post-primary schools, drawing attention to the limited Irish assessment-related research being conducted in both contexts. We then explore assessment developments related to Irish primary physical education and post-primary physical education and compare the extent to which such developments are limited in comparison to international assessment interests and practices in physical education. We conclude with suggestions related to studying (pre-service) teachers' and students' exposure to assessment in order to understand how we could alter the balance of assessment purposes and uses in Irish schools.